2018
DOI: 10.1055/s-0038-1625957
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Coagulation Changes at Early Stage after Total Knee Arthroplasty

Abstract: Coagulation changes after total knee arthroplasty (TKA) can provide evidence for optimization of timing of perioperative anticoagulation medicine. To evaluate the changes, 50 patients with knee osteoarthritis or rheumatoid arthritis were recruited for the study and underwent thrombelastography tests pre-, 6 hours, 12 hours, and 24 hours after TKA surgery and Doppler ultrasound examination 20 to 24 hours after surgery. The results have shown prolonged clotting time ( value) at 6 and 12 hours, while shortened at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…49 Huang et al also used TEG to test the changes in coagulation function within 24 h after total knee replacement. 50 Although the data obtained by the two groups were slightly different at approximately 24 h, the conclusions of these studies were similar. They believed that most coagulation functions of patients after joint replacement were in a low coagulation state within 24 h after the operation.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…49 Huang et al also used TEG to test the changes in coagulation function within 24 h after total knee replacement. 50 Although the data obtained by the two groups were slightly different at approximately 24 h, the conclusions of these studies were similar. They believed that most coagulation functions of patients after joint replacement were in a low coagulation state within 24 h after the operation.…”
Section: Introductionmentioning
confidence: 62%
“…Aspirin (ASA), an inhibitor of cyclooxygenase-1 (COX-1), reduces thrombosis by irreversibly inhibiting platelet aggregation and inhibits intimal hyperplasia. 50 , 63 In an experiment to explore the perioperative medication safety of ASA, Li et al found that during the perioperative period of posterior lumbar fusion, compared with the aspirin-free group (Group 2), the R and K of patients in the aspirin-extended group (Group 1) were relatively increased and MA and α-angles were relatively decreased, and they were not statistically significant. This conclusion is consistent with the outcomes of CCT of patients in the two groups and confirmed with the incidence of objective events.…”
Section: Introductionmentioning
confidence: 99%